Are uranium-contaminated soil and irrigation water a risk for human vegetables consumers ? A study case with Solanum tuberosum L., Phaseolus vulgaris L. and Lactuca sativa L. - Neves, O. (2015)
The knowledge of uranium concentration, in the products entering the human diet is of extreme importance because of their chemical hazard to health. Controlled field experiments with potatoes, beans and lettuce (Solanum tuberosum L., Phaseolus vulgaris L. and Lactuca sativa L.) were carried out in a contaminated soil used by local farmers located near a closed Portuguese uranium mine (Cunha Baixa, Mangualde). The soil with high average uranium levels (64–252 mg/kg) was divided in two plots, and irrigated with non-contaminated and uranium-contaminated water (\20 and [900 lg/L). Uranium maximum average concentration in the edible vegetables parts (mg/kg fresh weight) ranged in the following order: lettuce (234 lg/kg)[green bean (30 lg/kg)[potatoes without peel (4 lg/kg). Although uranium in soil, irrigation water and vegetables was high, the assessment of the health risk based on hazard quotient indicates that consumption of these vegetables does not represent potential adverse (no carcinogenic) effects for a local inhabitant during lifetime